Physical activity for the development of math skills in elementary school students (Innovaciones Educativas, 2024)
This paper aims to demonstrate the formative value of physical movement in pedagogical mediation processes of mathematical skills in elementary school students. This research was conducted with the faculty of the Sancti Spíritus Educational System, in the canton of Esparza, province of Puntarenas, Costa Rica. The research is based on theoretical principles that prove that physical movement is a central element of learning during childhood and contributes to the integral strengthening of cognitive, psychomotor and social skills and abilities. The qualitative approach used for the selection of the instruments and analysis of the information collected, concludes that for the group of participants, body movement is infrequent as a resource for the mediation of mathematical skills. This suggests that the concept of memorization should be abandoned and instead the pedagogical mediation of the subject should be rethought from an open, dynamic, creative, effective and quality curriculum. The innovative pedagogical approach must respond to the principles of a transformative education, that from the body movement (understood as the natural abilities to jump, turn, walk, run, maintain balance, coordination and the ability to concentrate), make each student the protagonist of their individual learning, allowing physical, emotional and cognitive unification.
Keywords: Mathematics; Elementary Education; Educational Environment; Learning; Teaching